Anesthesiology Airway-related Medicolegal Cases From the Canadian Medical Protection Association. Issue 4 (22nd December 2021) - Crosby, E.T.; Duggan, L.V.; Finestone, P.J.; Liu, R.; De Gorter, R.; Calder, L.A.
Abstract : ( Can J Anesth . 2021;68:183–195) The practice of anesthesiology has changed dramatically over the years, with new technology and updated strategies to manage and improve patient safety. The continual evaluation of patient outcomes and the development of protocols and guidelines help to further evolve the practice. One area worth reviewing is airway management. Anesthesiologists can learn from critical incidences described in malpractice cases to inform initiatives that drive patient safety. The aim of this paper was to describe closed claims legal cases involving anesthesiologists and airway-related management in Canada.